World almanac and book of facts 2025 - Janssen, Sarah 1982- (New York World Almanac Books, 2025)
The 2025 edition of The World Almanac reviews the biggest events of 2024 and will be your go-to source for questions on any topic in the upcoming year. Get thousands of facts at your fingertips with this essential resource: sports, pop culture, science and technology, U.S. history and government, world geography, business. This compendium of facts and statistics also provides a quick look at the surprising stats and curious facts that define the changing world.--
2024 Special features and year in review -- 2024: Year in pictures -- Economy, business, & energy -- Crime -- Military affairs -- Food & agriculture -- Health & vital statistics -- Personalities, arts & media -- Science & technology -- Consumer information -- U.S. facts & history -- World maps & flags -- U.S. government -- U.S. cities, states, & population -- World history & culture -- International statistics & nations of the world -- Sports -- General index
Includes index
115360
Keywords: Almanacs, American; United States -- Statistics; Reference works; Almanacs; Statistics; Encyclopedias